Legal Analysis of Transaction Security in The Metaverse: Consumer Protection Challenges in The Virtual World - Lufiano Tilman Martins; Lala Hucadinota Ainul Amri; Darma Setiawan Putra (Politeknik Siber Cerdika Internasional, 2026)
This study aims to analyze legal protection for transaction security in the metaverse and the challenges faced by consumers in the virtual world. The method used is a normative juridical approach with a qualitative approach, combining the Statute Approach to examine laws and regulations, the Conceptual Approach to examine legal concepts related to digital assets, smart contracts, and cybersecurity, and the Comparative Approach to compare consumer protection practices and international regulations in other countries. The research focuses on analyzing the authority of cyber law in protecting users, evaluating the effectiveness of existing regulations, identifying legal challenges resulting from the unique characteristics of the metaverse, and developing legal policy recommendations. The results show that national regulations provide basic protection, but are still limited in addressing the unique risks of virtual transactions, such as digital fraud, hacking, and smart contract disputes. Key legal challenges include cross-border jurisdiction, the legal status of digital assets, and the security of immersive data. This study recommends regulatory updates, transaction security standards, digital dispute resolution mechanisms, and cross-jurisdictional collaboration to strengthen consumer protection. The implications of this research provide a basis for developing adaptive cyber law policies in Indonesia and serve as a reference for international practices in regulating transactions in the metaverse.